The Role of Open and Distance Education in Digital Ecosystem Transformation: A Qualitative Study on Enhancing Educational Accessibility - Yasir Riady; Melisa Arisanty; Eko Kuswanti; Sri Sukatmi; Muhammad Firman Karim; Muhammad Ajmal (IJOEM: Indonesian Journal of E-learning and Multimedia, 2025)
Background of study: The use of Open and Distance Education (ODE) has become an essential approach for enhancing educational accessibility, especially in isolated regions. Aims and scope of the paper: This paper aims to support the efficacy of ODE in rural regions should concentrate on evaluating the influence of infrastructure on learning outcomes in rural environments through access to technology.Methods: This method used a qualitative study, which allows learners to progress at their speed and convenience, diminishing reliance on conventional educational infrastructure, which is frequently constrained in rural areas. ODE enables instructors to engage a broader audience through economical resources. Results: Its performance depends on critical elements such as internet connectivity, teacher readiness, and favorable government regulations. Conclusion: Utilizing appropriate tactics, Open and Distance Education can function as a viable alternative for improving educational quality and accessibility, hence cultivating an empowered and informed society, even in the most isolated regions.